The elephant and the dragon : the rise of India and China and what it means for all of us - Meredith, Robyn (New York : W.W. Norton, 2007)
Today, India is as near as the voice answering an 800 number for one dollar an hour, and China is as close as the nearest Wal-Mart. Not since the United States rose to prominence a century ago have we seen such tectonic shifts in global power; but India and China are vastly different nations, with opposing economic and political strategies--strategies we must understand in order to survive in the new global economy. This book is the first to compare and contrast how these two Asian nations, each with more than a billion people, are spurring a new "gold rush," and what this will mean for the rest of the world.--From publisher description.
Introduction: tectonic economics -- Where Mao meets the middle class -- From the spinning wheel to the fiber-optic wire -- Made by America in China -- The Internet's spice route -- The disassembly line -- India's cultural revolution -- Revolution by dinner party -- Geopolitics mixed with oil and water -- A catalyst for competitiveness.
Includes bibliographical references (p. 219-236) and index.
Keywords: Globalization; India -- Economic conditions -- 21st century; India -- Foreign economic relations; China -- Economic conditions -- 2000-; China -- Foreign economic relations; United States -- Economic conditions -- 21st century; United States -- Foreign economic relations